A QUICK LOOK AT ACADEMIC READING - WILLEM SARAGIH (BAHAS, 2013)
Being able to read for information written in English is one most important skill for students, especially those who are in tertiary education. The reason is that students have no choice but do a lot of reading to fulfil the the mand of the course set by the lecturers. Even it can be said that, academically, the success of a student  depends a lot on his or her reading ability. For Indonesian students, with the limited English language proficiency they have, this is a true challenge since  they cannot avoid being  confronted with the various types of English texts in which a lot of information relevant to their academic purpose is exposed. Students at this level of education have to read for information from research findings which have been organized and documented. Each type of texts they are supposed to read, normally, has its own particular way of sentence and paragraph construction. In other words, the sentences and paragraphs contained in the text are governed by rules of academic discourse. Therefore, to enable the students to get the message that the writer has expressed in the text, they should be made familiar with the arrangement of a sentence, a paragraph and even an essay up to finally the so called a text book. This article presents some information about academic reading views. The discussion covers  some explanation about 1)  academic reading, 2) students’ major reading reading problems, and 3). developing students’ reading comprehension skills.   Key Words: academic reading, reading problem, reading comprehension development